Composition Shifts of Arbuscular Mycorrhizal Fungi between Natural Wetland and Cultivated Paddy Field. Issue 10 (26th November 2017) - Xu, Shangqi; Zhang, Jianfeng; Rong, Jun; Ma, Lina; Tian, Lei; Tian, Chunjie
ABSTRACT: The community assembly change of arbuscular mycorrhizal fungi (AMF) during the reclamation of wetlands to paddy fields is mostly unknown. In this study, we applied the high-throughput sequencing technique to investigate the composition of the AMF community in natural wetland (common wild rice and Leersia hexandra Swartz) and paddy field (Asian cultivated rice), as well as the soil elements effective on the community of AMF. Soil properties including soil organic carbon, available nitrogen (AN), available phosphorus (AP), available potassium, and pH were also measured. Operational taxonomic units (OTUs) of nine genera in four orders ( Glomerales, Diversisporales, Archaeosporales, and Paraglomerales ) of AMF were detected. All detected AMF genera were found in the wild rice wetland, while about half of the detected AMF genera were absent in paddy field; however, the absolute amount of total AMF in the paddy field and wetland was not different. Among all measured soil properties, AMF community was affected significantly by soil AN and AP. Results indicate that agricultural managements affect AMF community significantly, but do not have negative effects on the absolute amount of all the AMF genera. Soil AP may be the main factor resulting in the decreased AMF genus in paddy field. In addition, AMF may have contributed to the survival and evolution of plants.